Facile Conversion of α‐Amino Acids into α‐Amino Phosphonates by Decarboxylative Phosphorylation using Visible‐Light Photocatalysis. Issue 37 (4th August 2022) - Reich, Dominik; Noble, Adam; Aggarwal, Varinder K.
Abstract: Amino phosphonates exhibit potent inhibitory activity for a wide range of biological processes due to their specific structural and electronic properties, making them important in a plethora of applications, including as enzyme inhibitors, herbicides, antiviral, antibacterial, and antifungal agents. While the traditional synthesis of α‐amino phosphonates has relied on the multicomponent Kabachnik‐Fields reaction, we herein describe a novel and facile conversion of activated derivatives of α‐amino acids directly to their respective α‐amino phosphonate counterparts via a decarboxylative radical–polar crossover process enabled by the use of visible‐light organophotocatalysis. The novel method shows broad applicability across a range of natural and synthetic amino acids, operates under mild conditions, and has been demonstrated to successfully achieve the late‐stage functionalization of drug molecules. Abstract : The facile conversion of α‐amino acids to the respective α‐amino phosphonates via their redox active esters using organophotoredox catalysis is reported. A novel photocatalytic phosphorylation combines radical–polar crossover with Arbuzov‐type reactivity, providing an operationally simple, high yielding and general synthetic approach for the generation of α‐amino phosphonates.